Earth Science Research for the 21st Century: A Theme for the GeoCanada 2000 Meeting. Actions on Collaboration, NSERC Reallocation and New Mega projects - Calvert, Stephen; Hall, Jeremy; Mayer, Larry (Geoscience Canada, 1999)
Summary A vigorous, high-quality earth science research community in Canada brings two rewards: great new concepts and tools for Canadians working in the resource and environmental sectors; and bright, energetic recruits to the profession that, in many disciplines, will be desperately needed when many of our present community retire in the next 15years. It is time for a new era of collaboration; it is time to respond constructively to the damaging cutbacks of NSERC Research Grants support of the earth sciences; and it is time to propound new large scale collaborative projects that catch the imagination of Canadians. In this article, we describe actions that are being taken now towards these goals, and we invite your participation in this venture, not least during the multi-society festival of the GeoCanada 2000 meeting.